Giovanni Botero on Religion and Politics - Zhu, Xin (Religions, 2024)
Giovanni Botero’s political thought is significantly influenced by Machiavelli, yet it possesses its own distinctive features, particularly in its religious perspective. In contrast to Machiavelli’s condemnation of Catholicism, Botero argues that Catholicism, far from weakening individuals, could instill in them the courage to defy death and foster military virtues through the promise of eternal life. While Botero agrees with Machiavelli that religion plays a central role in politics, he asserts that Catholicism is more effective than other sects as it is better suited to maintaining social order and disciplining the human conscience. However, he refutes the idea that religion should serve merely as an instrument of domination. Instead, he suggests that it should be the foundation of the state and the purpose of governance. Furthermore, he maintains that religion and the state are interdependent, functioning together to ensure the maintenance and advancement of both.